2004
DOI: 10.1002/ange.200353084
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Catalysis with Bimetallic Complexes: Robust and Efficient Catalysts for Atom‐Transfer Radical Additions

Abstract: Kharasch leichter gemacht: Zwei hocheffiziente Katalysatoren für radikalische Atomtransfer‐Additionen wurden durch paralleles Screening von Dimetallkomplexen gefunden. Beide Katalysatoren enthalten ein Rhodium‐Zentrum (blau), das über drei Chlorobrücken mit einem Ruthenium‐Zentrum (rot) verbunden ist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The observed TOFs are comparable to those of the best ATRA catalysts described so far, despite the low reaction temperature 21. In this context it is interesting to note that two other complexes containing a {RuNNRu} structural motif were reported to catalyze atom‐transfer radical reactions 21a. 22 For both complexes it was suggested that catalyst activation proceeds by a CCl 4 ‐induced loss of the N 2 ligand, and a similar mode of activation appears likely for reactions with 5 .…”
Section: Atra Reactions Catalyzed By 3/pcy3 or Bymentioning
confidence: 99%
“…The observed TOFs are comparable to those of the best ATRA catalysts described so far, despite the low reaction temperature 21. In this context it is interesting to note that two other complexes containing a {RuNNRu} structural motif were reported to catalyze atom‐transfer radical reactions 21a. 22 For both complexes it was suggested that catalyst activation proceeds by a CCl 4 ‐induced loss of the N 2 ligand, and a similar mode of activation appears likely for reactions with 5 .…”
Section: Atra Reactions Catalyzed By 3/pcy3 or Bymentioning
confidence: 99%
“…[5,6] Chloro-bridged Rh III ±Ru II complexes, for example, have been employed as highly efficient catalyst precursors for transfer hydrogenation, [5b] olefin metathesis, [5e] and atom-transfer radical additions (see below). [6] So far, investigations of the syntheses and structures of heterobimetallic, halogeno-bridged complexes have focused primarily on compounds with two halogeno bridges. [4] These complexes can easily be obtained in metathesis reactions starting from the corresponding homodimeric compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Due to the presence of the labile halogeno bridges, the complexes generally show high intrinsic reactivity, and some catalytic applications were recently reported. [5,6] Chloro-bridged Rh III ±Ru II complexes, for example, have been employed as highly efficient catalyst precursors for transfer hydrogenation, [5b] olefin metathesis, [5e] and atom-transfer radical additions (see below). [6] So far, investigations of the syntheses and structures of heterobimetallic, halogeno-bridged complexes have focused primarily on compounds with two halogeno bridges.…”
Section: Introductionmentioning
confidence: 99%